Promotion of the Warburg effect is associated with poor benefit from adjuvant chemotherapy in colorectal cancer. Issue 2 (9th January 2020) - Kitazawa, Masashi; Hatta, Tomohisa; Sasaki, Yusuke; Fukui, Kazuhiko; Ogawa, Koji; Fukuda, Eriko; Goshima, Naoki; Okita, Natsuko; Yamada, Yasuhide; Nakagama, Hitoshi; Natsume, Tohru; Horimoto, Katsuhisa
Abstract: Metabolic reprogramming, including the Warburg effect, is a hallmark of cancer. Indeed, the diversity of cancer metabolism leads to cancer heterogeneity, but accurate assessment of metabolic properties in tumors has not yet been undertaken. Here, we performed absolute quantification of the expression levels of 113 proteins related to carbohydrate metabolism and antioxidant pathways, in stage III colorectal cancer surgical specimens from 70 patients. The Warburg effect appeared in absolute protein levels between tumor and normal mucosa specimens demonstrated. Notably, the levels of proteins associated with the tricarboxylic citric acid cycle were remarkably reduced in the malignant tumors which had relapsed after surgery and treatment with 5‐fluorouracil‐based adjuvant therapy. In addition, the efficacy of 5‐fluorouracil also decreased in the cultured cancer cell lines with promotion of the Warburg effect. We further identified nine and eight important proteins, which are closely related to the Warburg effect, for relapse risk and 5‐fluorouracil benefit, respectively, using a biomarker exploration procedure. These results provide us a clue for bridging between metabolic protein expression profiles and benefit from 5‐fluorouracil adjuvant chemotherapy. Abstract : Using absolute quantification of protein levels, we identified that the behavior of Warburg effect‐related proteins was strongly associated with relapse prediction and the therapeutic indication of uracil‐tegafur (UFT)‐adjuvant therapy.